Prevalence of Clinical Study of Cutaneous Infection in Children - Jaber, Amin A. E. (Asian Journal of Clinical Pediatrics and Neonatology, 2017)
Background: Paediatric dermatoses are distinct group of disorders, comprising of skin problems encountered during childhood and adolescence. Skin diseases in the paediatric population are common all over the world. There is variation in the pattern and presentation of dermatoses, with eczemas being the most common skin disorder in developed countries and infections and infestations in the developing countries. Methods: Fifty children aged below 15 years, attending outpatient Department of Dermatology were included in this study. The diagnosis was made, based on detailed clinical history, general, systemic and cutaneous examination. Relevant investigations were carried out in necessary cases. The findings were recorded in proforma for analysis and interpretation of data. Results: In the present study, fifty children were included which were of below 15 year old. Among the fifty cases 30 (60%) were male and 20 (40%) were female. Out of 50 cases 4% 0-1 year, 10% 2-5 year, 20% 6-10 year and 26% 11-15 year old children were included. From the 50 patients, 58% were suffering from fungal infection, 24% from the viral infection and 18% from bacterial infection. Conclusion: This study conclude that, Proper sanitation, good hygiene, improving the nutritional status and creating health awareness can prevent infection.